Scavenging effect of EDTA-fluorocarbon microspheres on 210lead - Ding Xun-cheng; Liu Chun-fang; Dong Jing-wu; Du Jun; Wang Yi-cheng; Huang Xin (Acta Pharmacologica Sinica, 2016)
EDTA-fluorocarbon microspheres (EDTAFM), calcium disodium ethylene diaminetetraacetate (CaNa2EDTA), calcium- or zinc-diethylene triamine pentaacetate (Ca- or Zn-DTPA) were investigated for their ability to treat experimental lead intoxication in mice. The 48 ICR mice were divided into six groups. Group I = no treatment; The other groups were injected with single ip doses of 210Pb (10 mg Pb2+ +555 kBq/kg). After 24 h they were injected in the tail vein with the chelating agents (20 mg/kg) or an equal volume of 10% glucose (10 mg/kg). Each mouse was housed in one metabolic cage, and urine was collected daily for 3 d. After 3 d, the mice were sacrificed for comparison of lead distribution within the liver, kidney, femur and the entire carcass as measured by 0.047 Mev gamma emission from 210Pb. The results reveal that injection of EDTA-FM to lead poisoned mice pretreated with 210Pb was more effective than Zn- or Ca-DTPA and CaNa2EDTA in reducing the lead induced inhibition in the activity of blood ALAD, and that it increased the excretion of 210Pb into the urine. The hepatic, renal and femur 210Pb contents after treatment with EDTAFM were much more decreased than Zn- or Ca-DTPA and CaNa2-EDTA. The order of effectiveness was EDTAFM greater than Zn-DTPA greater than Ca-DTPA greater than CaNa2-EDTA.